Memória biocultural e sua articulação com os saberes escolares na Aldeia Nova Esperança, Manaus-AM. - Colares, Peterson Medeiros (2018)
ABSTRACT This work aims to study, from the perspective of the Biocultural Memory, the confluence between the scientific and traditional knowledge in the Puranga Pisasú School and how they reaffirm the identity of the baré people of Aldeia Nova Esperança, Manaus, Amazonas. It has its theoretical foundation backed by Toledo and Barrera-Bassols (2010, 2015) Foucault (1996, 1999, 2005, 2008), Bauman (2001, 2005), Hall (2003, 2005), Vasconcellos (2002), Meliá (1999) and others, to understand the debate about the production, circulation and validation of knowledge, the social status of scientific knowledge and its influence on the colonizing process of indigenous cultures, and the concept of Biocultural Memory as a variety of complex systems of knowledge and practices of subject-nature relationship that are established and updated from human composition to ecosystems over time. The research was characterized as a case study, with a qualitative-quantitative approach, using bibliographic and documentary research techniques, semi-structured interviews and direct observation. The results show that the school-community articulation around a work project, based on Project Pedagogy, has allowed to articulate, although in an incipient form, the contents of the formal curriculum with knowledge of the traditional culture, especially its symbolic and ritual aspects, contributing effectively to the resumption of customs and practices of baré culture in that community. . Key words. Biocultural Memory. Traditional Knowledge. Indigenous School Education.